Kinetic and isotherm studies of nickel and cadmium ions adsorption onto Clay-Chitosan composite - Rachid Et-Tanteny; Ibrahim Allaoui; Imad Manssouri; Bouchta El Amrani; Khalid Draoui (Results in Chemistry)
Ni (II) and Cd (II) ions pose a serious threat to the health of the planet and its inhabitants. They contaminate ecosystem, endangering the survival of many species, including humans. In this study, a novel clay-chitosan composite was prepared and characterized to evaluate its adsorption potential for the removal of these pollutants. The Ni (II) and Cd (II) concentrations were precisely determined using inductively coupled plasma atomic emission spectroscopy (ICP-AES). The obtained results revealed that the maximum adsorbed quantities obtained were 153.086 mg/g for Ni (II) and 61.093 mg/g for Cd (II), demonstrating the excellent performance of the composite. Nonlinear modeling of the kinetic and isotherm data demonstrated that the pseudo second order kinetic model best describes the adsorption kinetics of R2 = 0.994 for Cd (II) and R2 = 0.999 for Ni (II), with a rapid equilibrium time reached in 60 min. In addition, the Sips isotherm model best describes the adsorption isotherms of R2 = 0.993 for Cd (II) and R2 = 0.990 for Ni (II), suggesting a chemisorption mechanism involving a heterogeneous distribution of adsorption sites. The combination of clay and chitosan as a biocomposite represents a significant advance in water filtration, particularly in the manufacture of water treatment filters and offers a promising and environmentally friendly alternative to existing technologies for the removal of heavy metal contaminants.